PENGARUH CUSTOMER EXPERIENCE DAN CUSTOMER VALUE TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION - Hijjah, Risalatin; Ardiansari, Anindya (Management Analysis Journal, 2015)
The aims of this research are to analyze the direct and indirect influence of the customer experience, customer value and customer satisfaction on the customer loyalty at The Fountain Water Park & Resto. The sample size consist of 116 respondents with purposive judgement sampling through likert scale questionnaire. Percentage descriptive, multiple linier regression and path analysis were employed to analyze data. Significant results of this research indicate customer experience and customer value influence customer loyalty through customer satisfaction so can be concluded that mediation circuit occurs in this study. The conclusion of this research are proved that customer experience, customer value and customer satisfaction as the mediation influence by direct and indirect on the customer loyalty.